15.5k views
3 votes
Divide the sum of (-5), (-10) and (-9) by the product of 2 and (-3).

User SemanticUI
by
6.8k points

2 Answers

6 votes

Answer:

4

Explanation:

-5+(-10)+(-9)/2*(-3)

=-5-10-9/-6

=-24/-6

=4

User SollyBunny
by
7.4k points
4 votes

Answer:


\large \boxed{4}

Explanation:


\sf The \ sum \ of \ -5, \ -10, \ and \ -9 \ is \ divided \\ by \ the \ product \ or \ multiplication \ of \ 2 \ and -3.


\displaystyle (-5+-10+-9)/(2 * -3)


\displaystyle (-24)/(-6)


=4

User Chris Duncan
by
7.9k points